Refractive Error Characteristics in Patients with Congenital Blepharoptosis Before and after Surgery - Khan, Taimoor Ashraf; Shahid, Muhammad; Naeem, Saquib; Rauf, Abdul; Liaqat, Talha; Awais, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To surgically manage patients with congenital blepharoptosis and compare the refractive errors before and after intervention Study Design: Quasi-experimental study. Place and Duration of Study: Department of Orbit and Oculoplastic surgery, Armed Forces Institute of Ophthalmology Rawalpindi from February 2022 to December 2022. Methodology: Patients with congenital ptosis who underwent surgical management at our setup and those who stick to postoperative follow up for at least 6 weeks were included in the study. An average of 6 readings were taken of an automated refractometer to measure pre- and post-operative refractive error. Results: Out of total 20 patients, 11(55%) were males while 9(45%) were females. Age of patients who were surgically managed ranged from 3 to 13 years. All patients had pre-op diagnosis of unilateral simple congenital ptosis. There was significant difference (in terms of reduction of refractive error) in pre and post op refractive error measured in diopters. Conclusion: Congenital blepharoptosis may present as a wide variety of refractive errors and upper lid blepharoptosis surgery repair have shown to improve the refractive error secondary to induced astigmatism. However, no particular surgery technique is found to be superior to other in our study sample and all surgical procedures had proven to be safe and effective approach towards blepharoptosis repair.